The sense of dignity of care and the perceived social support for hospitalized elderly patients - Shahin Salarvand; Ali Hashemzadeh; Ali Delshad Noghabi (Elsevier, 2023)
Introduction: Hospitalization is a common experience among elders all over the world, which often is associated with a high level of stress. These stressors can affect Patient Dignity (PD). In addition, the elders rely on many social support networks for aging-related challenges. This study aimed to determine the relationship between PD and perceived social support (PSS) in hospitalized elders. Methods: In this cross-sectional study, the samples of this research were 360 older people 60 years old and older who were hospitalized in educational hospitals in Khorramabad city (Lorestan province in the western area of Iran). The applied instruments in this research included; demographic characteristics, PD, and the PSS questionnaires. Results: This study showed that %92.2 of hospitalized elders had at least one underlying disease. The men significantly had a lower sense of dignity in comparison with women. There was a significant statistical correlation between the increase in the PSS and the increase in the sense of dignity in elders. Conclusion: The elders perceived more social support and had more of a sense of dignity. The men had lower dignity in comparison with their women counterparts. Also, the elders who suffered an underlying disease had a lower sense of dignity.